Regulating behavioral spillovers: Regulatory focus moderates the link between perceived goal progress and engagement in subsequent behaviors - HUANG, Tengjiao (Institutional Knowledge at Singapore Management University, 2022)
Behavioral spillover occurs when performing an initial behavior increases the likelihood of performing a subsequent behavior (positive spillover) or decreases this likelihood (negative spillover). The current research focuses on negative spillovers of pro-environmental behaviors (PEB), which has the implication of limiting individuals’ environmental conservation efforts. To offer insights, three studies sought to explicate how and for whom negative spillovers would occur. I theorized that prior behaviors would negatively predict subsequent behaviors via greater perceived goal progress and that this negative association between perceived goal progress and subsequent engagement would be more pronounced for people with a strong (vs. weak) promotion focus. This is because promotion-focused individuals are more sensitive to gains (e.g., goal progress) and may discontinue their pursuits when they perceive a positive state has been attained (Zou et al., 2014). Across two studies, self-reported (Study 1, N = 161) and experimentally induced recall (Study 2, N = 481) of prior PEB led to greater perceived goal progress. However, its effect varied with a stronger promotion focus accentuating a negative spillover for PEB intentions in Study 1 but a positive spillover for environmental donation in Study 2. As Study 1 referenced a general collective goal of addressing climate change and Study 2 referenced a personal goal of addressing climate change, Study 3 (N = 501) sought to examine whether the observed differing spillover effects would be moderated by goal framing (i.e., collective vs. personal goal). Negative spillovers may be more pronounced for collective (vs. personal) goals as people feel that they can be relieved of the responsibility for expending further effort toward the collective goals if they have previously contributed. However, Study 3 could not reconcile the inconsistent spillover patterns found in Studies 1 and 2. The implications of these findings and future directions are discussed.